2019
DOI: 10.3390/w11081532
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrochemical Systems for Groundwater Remediation: The Development Trend and Research Front Revealed by Bibliometric Analysis

Abstract: : Due to the deficiency of fresh water resources and the deterioration of groundwater quality worldwide, groundwater remedial technologies are especially crucial for preventing groundwater pollution and protecting the precious groundwater resource. Among the remedial alternatives, bioelectrochemical systems have unique advantages on both economic and technological aspects. However, it is rare to see a deep study focused on the information mining and visualization of the publications in this field, and research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 175 publications
(225 reference statements)
0
11
0
Order By: Relevance
“…In addition, articles by Holmes et al [15], Wu et al [18], Vrionis et al [20], Caporaso et al (This is a letter.) [21], and Reguera et al [22] cannot be found by the searching strategy in the original paper [1].…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…In addition, articles by Holmes et al [15], Wu et al [18], Vrionis et al [20], Caporaso et al (This is a letter.) [21], and Reguera et al [22] cannot be found by the searching strategy in the original paper [1].…”
mentioning
confidence: 98%
“…Li et al recently published a paper in Water entitled "Bioelectrochemical systems for groundwater remediation: The development trend and research front revealed by bibliometric analysis" [1]. Li et al mentioned searching strategy in Section 2.1.…”
mentioning
confidence: 99%
See 3 more Smart Citations